Inorganic elements in green sea turtles (Chelonia mydas): Relationships among external and internal tissues. (30th July 2014) - Faust, Derek R.; Hooper, Michael J.; Cobb, George P.; Barnes, Melanie; Shaver, Donna; Ertolacci, Shauna; Smith, Philip N.
Abstract Inorganic elements from anthropogenic sources have entered marine environments worldwide and are detectable in marine organisms, including sea turtles. Threatened and endangered classifications of sea turtles have heretofore made assessments of contaminant concentrations difficult because of regulatory restrictions on obtaining samples using nonlethal techniques. In the present study, claw and skin biopsy samples were examined as potential indicators of internal tissue burdens in green sea turtles (Chelonia mydas). Significant relationships were observed between claw and liver, and claw and muscle concentrations of mercury, nickel, arsenic, and selenium (p < 0.05). Similarly, significant relationships were observed between skin biopsy concentrations and those in liver, kidney, and muscle tissues for mercury, arsenic, selenium, and vanadium (p < 0.05). Concentrations of arsenic, barium, chromium, nickel, strontium, vanadium, and zinc in claws and skin biopsies were substantially elevated when compared with all other tissues, indicating that these highly keratinized tissues may represent sequestration or excretion pathways. Correlations between standard carapace length and cobalt, lead, and manganese concentrations were observed (p < 0.05), indicating that tissue concentrations of these elements may be related to age and size. Results suggest that claws may indeed be useful indicators of mercury and nickel concentrations in liver and muscle tissues, whereas skin biopsy inorganic element concentrations may be better suited as indicators of mercury, selenium, and vanadium concentrations in liver, kidney, and muscle tissues of green sea turtles. Environ Toxicol Chem 2014; 33:2020–2027. © 2014 SETAC